Analysis of a Chlamydia epidemic model with pulse vaccination strategy in a random environment - Guruprasad Samantaa; Shyam Pada Bera (Nonlinear Analysis, 2018)
In this paper, we have considered a dynamical model of Chlamydia disease with varying total population size, bilinear incidence rate, and pulse vaccination strategy in a random environment. It has been shown that the Chlamydia epidemic model has global positive solutions and, under some conditions, it admits a unique positive periodic disease-free solution, which is globally exponentially stable in mean square. We have defined two positive numbers R1 and R2 (< R1). It is proved that the susceptible population will be persistent in the mean and the disease will be going to extinct if R1 < 1 and the susceptible population as well as the disease will be weakly persistent in the mean if R2 > 1. Our analytical findings are explained through numerical simulation, which show the reliability of our model from the epidemiological point of view.